Sistem E-Inventory Menggunakan Bahasa Pemograman Visual Basic.NET - Muhardi Muhardi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
Universal Computer is a business entity in Pekanbaru engaged in the assembly and sale of computers and equipment that do not have a system that integrates well between sales, purchases, and inventory. The recording process is still manual by using the ledger so that the resulting data is less effective and efficient. In addition, the Universal Computer Shop has a weakness in reporting sales, purchases, and inventory that the level of accuracy is still lacking. Entities such as Universal Computer Store will be very good if they have a good information system so that the management of sales, purchases, and inventory in the business will be better. This information system is based on desktop using visual basic programming language .Net and SQL Server 2008 database and information system design that used is Data Flow Diagram (DFD) and ER diagram for business process to be designed. Information systems are provided for Universal Computer Stores to provide convenience to system users, especially employees, suppliers, customers, inventory, goods, and sales, purchasing, sales, inventory, employees, suppliers and customers. It can be concluded that this application is able to assist the Universal Computer Shop in handling the problem of recording purchases, sales, management, inventory, employees, suppliers, customers making reports on purchases, sales, inventory, employees, suppliers, and customers. Keywords: Purchase, Sales, Inventory, Visual Basic. Net, SQL Server 2008